Marmota camtschatica - Robert S. Hoffmann; Charles G. Anderson (Smithsonian Institution Press, 1993)
Marmota camtschatica (Pallas, 1811). Zoogr. Rosso-Asiat., p. 156. TYPE LOCALITY: " Kamchatka " [Kamchatsk. Obi., Russia]. DISTRIBUTION: E Siberia from Transbaikalia to Chukotka and Kamchatka (Russia), in several geographically isolated populations (Nikol'skii et al., 1991). SYNONYMS: bungei (Kastschenko, 1901); cliftoni (Thomas, 1902); doppelmayeri Birula, 1922. COMMENTS: Regarded as a synonym of marmota (Ellerman and Morrison-Scott, 1951; Rausch, 1953). Hoffmann et al. (1979) reviewed this and related species, and affirmed its specific status. Kapitonov (1978) concluded that morphological differences justified independent specific status for doppelmayeri, but Nikol'skii et al. (1991) showed similarity of vocalization between it and bungei, while the nominate form differed, and recommended that doppelmayeri be retained provisionally in this species. Published as part of Robert S. Hoffmann & Charles G. Anderson, 1993, Order Rodentia - Family Sciuridae, pp. 419-465 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 431, DOI: 10.5281/zenodo.7353130